Quasi-static Eocene-Oligocene climate in Patagonia promotes slow faunal evolution and mid-Cenozoic global cooling - Khon, Matthew J.; Stromberg, Caroline; Madden, Richard H.; Dunn, Regan E.; Evans, Samantha; Palacios, Alma; Carlini, Alfredo Armando (Palaeogeography, Palaeoclimatology, Palaeoecology)
New local/regional climatic data were compared with floral and faunal records from central Patagonia to investigate how faunas evolve in the context of local and global climates. Oxygen isotope compositions of mammal fossils between c. 43 and 21Ma suggest a nearly constant mean annual temperature of 16±3°C, consistent with leaf physiognomic and sea surface studies that imply temperatures of 16-18°C. Carbon isotopes in tooth enamel track atmospheric δ13C, but with a positive deviation at 27.2Ma, and a strong negative deviation at 21Ma. Combined with paleosol characteristics and reconstructed Leaf Area Indices (rLAIs), these trends suggest aridification from 45Ma (c. 1200mm/yr) to 43Ma (c. 450mm/yr), quasi-constant MAP until at least 31Ma, and an increase to ~800mm/yr by 21Ma. Comparable MAP through most of the sequence is consistent with relatively constant floral compositions, rLAI, and leaf physiognomy. Abundance of palms reflects relatively dry-adapted lineages and greater drought tolerance under higher pCO2. Pedogenic carbonate isotopes imply low pCO2=430±300ppmv at the initiation of the Eocene-Oligocene climatic transition. Arid conditions in Patagonia during the late Eocene through Oligocene provided dust to the Southern Ocean, enhancing productivity of silicifiers, drawdown of atmospheric CO2, and protracted global cooling. As the Antarctic Circumpolar Current formed and Earth cooled, wind speeds increased across Patagonia, providing more dust in a positive climate feedback. High tooth crowns (hypsodonty) and ever-growing teeth (hypselodonty) in notoungulates evolved slowly and progressively over 20Ma after initiation of relatively dry environments through natural selection in response to dust ingestion. A Ratchet evolutionary model may explain protracted evolution of hypsodonty, in which small variations in climate or dust delivery in an otherwise static environment drive small morphological shifts that accumulate slowly over geologic time. Fil: Khon, Matthew J. Boise State University; Estados Unidos ...